Histological Implications in Anabas testudineus (Bloch, 1792) upon Exposure to Cypermethrin (25% EC) - Kishor Kunal; Parvaiz Ahmad Ganie; Garima; Pramod Kumar Pandey (Journal of Indian Fisheries Association, 2019)
In the aquatic environment, fishes are one of the most important members of the aquatic food chain, and through them, some toxicants may reach human beings as well. As fishes are presumed to be the most understood organisms in the aquatic environment and as they are sensitive to pollution, fishes qualify to be the most suitable and popular test organisms among other animal groups. Climbing perch (Anabas testudineus) is gaining popularity as a table fish in India and is considered a delicacy in some north-eastern states, especially Manipur, Assam, Tripura and West Bengal. The present study was carried out to investigate the eﬀects of cypermethrin on gill histopathology in A. testudineus. The 24 hr LC50 value of cypermethrin in A. testudineus was found to be 17.1 µg/L. Three sublethal concentrations i.e. 4.275, 1.71 and 0.171 µg/L corresponding to 25, 10, and 1% of 24 hrs LC50 were used for 45 days chronic studies. Histopathological changes in gills, like clubbing of cells, hyperplasia, fusion of secondary lamellae followed by intense blood congestion and degeneration of primary and secondary gill lamellae confirm the toxic eﬀects of cypermethrin in the test fish.